Analysis of methods for determining the total costs of imports for exports using tables «input – output» - Karatkevich, Alexey I.; Lapko, Boris V.; Shparun, Dina V. (Journal of the Belarusian State University. Economics, 2025)
The article analyses the existing methods for determining the full cost of imports for exports, provides a comparative analysis of these methods, and identifies their main advantages and disadvantages. Based on the tables «input – output» of Sweden and Germany for 2018, the article calculates the full cost of imports for exports using the three methods discussed and examines the differences in the resulting values.
Keywords: import; export; tables «input – output»; full cost of imports; full cost coefficients